Karakter Vegetatif Kacang Koro Pedang (Canavalia ensiformis L.) pada Kondisi Naungan dan Pemupukan yang Berbeda - Azfani Nelza; Tatiek Kartika Suharsi; Memen Surahman (JURNAL AGROTEKNOLOGI UNIVERSITAS ANDALAS, 2018)
Specific changes in morphology, anatomy, biochemistry and molecular occur due to changes in light intensity. Changes in growth is closely related to the mechanism of plant resistance when low light conditions. In addition, the environmental stress conditions of supply nutrients plants need in order to remain able to grow optimally. This experiment was conducted in experimental garden Sawah Baru, Post-harvest Laboratory and Micro-engineering Laboratory Bogor Agricultural University, beginning in December 2014 until July 2015. This experiment was aims to determine the effect of shade and fertilization on the growth and change of morpho-anatomy of leaves jack bean. The experiment was arranged in a split plot design based on randomized complete block design. Shade as the main plot that consists of three levels: without shade, shade 25% and 50% and combination doses of fertilizer as a subplot which consists of three levels ie: 50 kg urea ha-1 + 100 kg SP-36 ha-1 + 75 kg KCl ha-1, 75 kg urea ha-1 + 125 kg SP-36 ha-1 + 100 kg KCl ha-1, 100 kg urea ha-1 + 150 kg SP-36 ha-1 + 125 kg KCl ha-1.The results showed increased percentage of shade caused etiolation, reduction number of branches, change the leave size, depletion of palisade tissue which decreases the thickness of the leaves, and decreased of pod/plant.Whilefertilizationfactoronlyinfluence onthe thickleaves andthickpalisade.